Characterization and in vitro evaluation of bacterial cellulose membranes functionalized with osteogenic growth peptide for bone tissue engineering - Saska, Sybele [UNESP]; Scarel-Caminaga, Raquel Mantuaneli [UNESP]; Teixeira, Lucas Novaes; Franchi, Leonardo Pereira; dos Santos, Raquel Alves; Minarelli Gaspar, Ana Maria [UNESP]; de Oliveira, Paulo Tambasco; Rosa, Adalberto Luiz; Takahashi, Catarina Satie; Messaddeq, Younes [UNESP]; Lima Ribeiro, Sidney Jose [UNESP]; Marchetto, Reinaldo [UNESP] (Springer, 2012)
The aim of this study was to characterize the physicochemical properties of bacterial cellulose (BC) membranes functionalized with osteogenic growth peptide (OGP) and its C-terminal pentapeptide OGP[10-14], and to evaluate in vitro osteoinductive potential in early osteogenesis, besides, to evaluate cytotoxic, genotoxic and/or mutagenic effects. Peptide incorporation into the BC membranes did not change the morphology of BC nanofibers and BC crystallinity pattern. The characterization was complemented by Raman scattering, swelling ratio and mechanical tests. In vitro assays demonstrated no cytotoxic, genotoxic or mutagenic effects for any of the studied BC membranes. Culture with osteogenic cells revealed no difference in cell morphology among all the membranes tested. Cell viability/proliferation, total protein content, alkaline phosphatase activity and mineralization assays indicated that BC-OGP membranes enabled the highest development of the osteoblastic phenotype in vitro. In conclusion, the negative results of cytotoxicity, genotoxicity and mutagenicity indicated that all the membranes can be employed for medical supplies, mainly in bone tissue engineering/regeneration, due to their osteoinductive properties.